A rare case of an isolated PAX6 mutation, aniridia, and Wilms tumor. (4th March 2021) - Lind, Katherine T.; Cost, Nicholas G.; Zegar, Kelsey; Kuldanek, Susan A.; Enzenauer, Robert W.; Schneider, Kami W.
ABSTRACT: Introduction: Wilms tumor (WT) is the most common renal malignancy of children and can be seen in WAGR syndrome (WT, aniridia, genitourinary anomalies, and intellectual disability). WAGR results from a contiguous gene deletion within the 11p13 region, encompassing the WT1 gene, often responsible for WT development, and the PAX6 gene, responsible for aniridia. Aniridia, a pan-ocular disease resulting from iris hypoplasia, is thought to increase the risk for WT development if their genetic alteration spans both the WT1 and the PAX6 genes on 11p13. Case Description: We describe a unique case of a patient with aniridia secondary to a heterozygous PAX6 nonsense mutation who developed WT despite no additional identifiable germline genetic drivers for this disease. Discussion: Isolated mutations in PAX6 previously have not been associated with increased risk of WT development case raises the question of if surveillance for WT should be continued in patients with aniridia with an isolated PAX6 mutation identified.